Hydrogeology of the Pearl River Delta, southern China. Issue 2 (9th December 2020) - Lancia, Michele; Su, Huang; Tian, Yong; Xu, Jintai; Andrews, Charles; Lerner, David N.; Zheng, Chunmiao
ABSTRACT: The study describes the hydrogeological setting of the Pearl River Delta, a sub-tropical area of southern China encompassing the metropolises of Guangzhou, Shenzhen, Hong Kong and Macau. In the last 40 years, a booming economy and a population of about 60 million has increased water demand satisfied by a huge system of dams and reservoirs. Aquifers in the studied area are underutilized and only a few recent studies have addressed hydrogeological characterization at a local scale. Understanding groundwater dynamics of the Pearl River Delta is important for developing additional water supplies, understanding and mitigating groundwater pollution, and for implementing 'Sponge City' concepts. Via a collection of data from literature and field surveys, the hydrogeological setting of the area is synthetized and represented through thematic maps, cross sections and a hydro-stratigraphic column. Hydrogeological conceptual models are developed that describe the groundwater dynamics in urban and rural areas within the Pearl River Delta.